Quantitative evaluation of individual food intake by insectivorous vespertilionid bats (Chiroptera, Vespertilionidae) - Marharyta Moiseienko; Anton Vlaschenko (Biology Open, 2021)
Insectivorous bats provide important ecosystem services, especially by suppressing and controlling the insects’ biomass. To empirically quantify the number of insects consumed by European vespertilionid bats per night, we estimated their ratio of dry mass of feces to mass of consumed insects. This study combines the results of feeding in captivity and the data obtained in field surveys; dry mass of feces was measured in both cases. In captivity, we analyzed the effect of species, age and sex of bats, species of insects consumed and the mass of food portion on the dry mass of feces. Using coefficients of the regression model, we estimated the number of insects consumed by free-ranging bats based on dry mass of their feces. According to our estimates, on average, one individual of one of the largest European bat species, Nyctalus noctula, consumes 2.2 g (ranging from 0.5 to 8.2 g) of insects per one feeding night, while the smallest European bats of genus Pipistrellus consume 0.4 g (ranging from 0.1 to 1.3 g), further confirming the importance of insectivorous bats for ecosystem services. This publication offers the novel method for the estimation of insects’ biomass consumed by bats.